Legal Reform of Airsoft Gun Regulation in Indonesia: Comparative Lessons from Portugal - Soeryono, Hery (DiH: Jurnal Ilmu Hukum, 2025)
The massive distribution of Airsoftguns in the community and the increasing number of cases of abuse due to free distribution make it necessary to have massive supervision in the distribution of airsoftguns and ambiguity in law enforcement regarding the misuse of airsoft guns, especially if there are no additional provisions detailing the regulation of non-standard weapons, so research This aims to analyze authority and preventive efforts in law enforcement with the research method used is normative juridical using secondary legal data. The results of the research show that there is a need for revisions related to regulations on the use of airsoft guns and the authority to track the distribution of airsoft guns by the police as well as socialization under the police regarding the use of airsoft guns in Indonesia.